Evil genius of feminism: Nietzsche’s origins of woman - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
The article is a commentary and an additional research on the Russian translation of an article by the American philosopher Robert С. Golub, published in this journal. The article discusses the concept of power and the concept of value in the Nietzschean project to overcome of man and how it conception deals with feminist philosophy